Efektifitas Media Video dalam Meningkatkan Pengetahuan Perubahan Psikologi Remaja di SMK Setiabudhi Semarang - Lia Mulyanti; Anisa Rochmawati; Ariyani Lutfitasari; Fitriani Nur Damayanti (Yayasan Literasi Sains Indonesia, 2025)
Background: Knowledge of psychological changes is necessary for adolescents. If the knowledge of adolescents can be fulfilled, it will bring happiness and success in completing the next developmental tasks. Conversely, if they do not understand about psychological changes and fail to adapt, it will cause unhappiness in the teenager concerned, and difficulties in completing the developmental tasks of the following periods. Increasing adolescent knowledge can be done by counseling using video media. Objective: To analyze the effectiveness of using video media in increasing knowledge of adolescent psychological changes at SMK Setiabudhi Semarang. Methods: This type of research is quantitative research with quasi experiment method with design using one group pretest posttest design. Results: Before being given a video about psychological changes, it was found that most respondents had moderate knowledge at 53%. After being given a video about psychological changes, most respondents had a high level of knowledge at 49.6%. The results showed that video media on psychological changes was effective in increasing the knowledge of adolescents at SMK Setiabudhi Semarang, with a p value: 0.000 (<0.05). Conclusion: Providing information through video media about psychological changes is effective in increasing adolescent knowledge at SMK Setiabudhi Semarang.